Griscelli syndrome type 2: The first reported case of compound heterozygous mutation in RAB 27 A gene from India (Indian Journal of Case Reports, 2019)
Griscelli syndrome (GS) is a rare autosomal recessive disorder resulting in pigmentary dilution of the skin and hair with variable phenotypes depending upon the underlying genetic mutation. Mutations in 3 distinct genes MYO5A, RAB27A, MLPH are responsible for 3 subtypes (GS1, GS2, and GS3) of GS respectively. Griscelli syndrome type 2 (GS-2) is a rare autosomal recessive disease. It commonly presents with hemophagocytic lymphohistiocytosis (HLH) and recurrent infections due to immunodeficiency. We describe a 3-year-old female with pyrexia, silvery hair, lymphadenopathy, hepatosplenomegaly, and hemophagocytosis. We found a novel compound heterozygous mutation in the RAB 27A gene. She succumbed despite being on dexamethasone and septran prophylaxis. This case spreads awareness about this rare potentially fatal disease, as a high index of suspicion is required for prompt diagnosis and treatment. Early bone marrow transplant is the only curative treatment for GS-2.